Immunosenescence and inflammaging: Mechanisms and modulation through diet and lifestyle - Müller, Ludmila; Di Benedetto, Svetlana (Frontiers in Immunology, 2025)
Aging is associated with profound alterations in the immune system, characterized by immunosenescence and inflammaging, which together compromise host defense, promote chronic low-grade inflammation, and contribute to the development of age-related diseases. Immunosenescence involves thymic involution, hematopoietic stem cell skewing, accumulation of senescent immune cells, and impaired adaptive and innate responses. Inflammaging arises from persistent activation of innate immune pathways, senescence-associated secretory phenotype (SASP) signaling, metabolic dysregulation, and age-related alterations in the gut microbiome. These processes are interconnected through feedback loops and network-level interactions among immune, metabolic, and microbial systems, creating a self-perpetuating cycle of immune dysfunction and systemic inflammation. Emerging evidence indicates that immunosenescence and inflammaging can be modulated through integrative strategies that combine nutrition, microbiome modulation, and lifestyle interventions to sustain immune resilience across the lifespan. Nutrient-specific strategies, including polyphenols, omega-3 fatty acids, and micronutrients, regulate oxidative stress, cytokine signaling, and immune cell metabolism. Holistic dietary patterns such as the Mediterranean diet, caloric restriction, and microbiome-supportive diets enhance gut barrier integrity, modulate systemic inflammation, and improve adaptive immunity. Lifestyle factors, including regular physical activity, adequate sleep, and stress reduction, further support immune resilience. Personalized nutrition and lifestyle strategies, guided by immunobiological profiling, enable tailored approaches to mitigate immune aging. Collectively, these insights highlight a multidimensional framework for understanding and modulating immunosenescence and inflammaging. Integrating dietary, lifestyle, and pharmacological strategies offers a promising path toward enhancing immune function, reducing chronic inflammation, and promoting healthy longevity.